Improvement of Hydro-Meteorological Products and Services in Viet Nam: Situation Appraisal and Policy Recommendation Application - N. Quang T. Thuy; N. D. Quang; D. Q. Tri; B. M. Ha; H. P. Cuong; D. V. Trong; H. D. Cuong (International Association of Lowland Technology, 2019)
Rapidly developing tropical countries such as Viet Nam are experiencing a rapid demand for hydro-meteorological information services. Evaluation of end-users’ demands is one way to inform policy development for organizations such as the Viet Nam Meteorological and Hydrological Administration so that they can provide the most relevant and useful products and services to the diverse and evolving market. An initial interview survey was conducted across 18 provinces and cities in Viet Nam between October and November 2017 to elicit information that would improve understanding of end-users’ perception of the importance of hydro-meteorological information, the quality and utility of current products and services, and expectations for development of hydro-meteorological information over the near future. The results indicated that the contents of the bulletins or the speed of access on TV or the website of the National Center for Hydro-meteorological Forecasting) need to be improved to meet the needs of the wide range of users. Furthermore, the end-users will be happy to pay if the information is accurate and timely. Experience from this initial survey will be used to expand the interview survey to the national scale, covering all 63 provinces and 5 centrally-controlled municipalities, and to increase the range of stakeholders’ participation.